ASSOCIATION BETWEEN ANXIETY, FOOD ADDICTION AND PHYSICAL ACTIVITY WITH THE CONSUMPTION OF ULTRA-PROCESSED FOODS AMONG UNIVERSITY STUDENTS (REMUNOM, 2025)
The NOVA classification defines ultra-processed foods as industrial formulations with artificial ingredients that promote greater palatability and shelf life. Excessive consumption of these foods is associated with weight gain, anxiety, and unhealthy eating habits in college students. The aim of the present study was to understand the factors that influence the consumption of UPF by college students by investigating the relationship between anxiety, food addiction, and physical activity. This study only included adults aged between 18 and 59 years. Data on social, anthropometric, anxiety, food addiction, physical activity, eating habits were collected using the Food and Nutrition Surveillance System questionnaire, and food consumption using the NOVA-UPF tool. A total of 100 students were included in our analyses, 89% of whom were female, 54% classified as sufficiently active, 45% with generalized anxiety disorder, and 9% with food addiction. It was possible to observe associations between anxiety and the score with the NOVA-AUP tool (β = 1.20; 95% CI = 0.17; 2.22; p = 0.02), dietary habits and subgroups of ultra-processed foods. Associations were also identified between food addiction and the NOVA-UPF score (β = 2.75; 95% CI = 1.01; 4.50; p < 0.01), as well as subgroups of ultra-processed foods. No associations were observed with the level of physical activity. Thus, strategies such as nutritional education based on culinary skills, combined with psychological support, seem to be able to help reduce the consumption of ultra-processed food and improve the general well-being of students.